How Interest Rates Changed under Financial Liberalization : A Cross-Country Review - Honohan, Patrick (World Bank, Washington, DC, 2014)
Financial liberalization was expected to make interest rates, and asset prices more volatile, with distributional consequences, such as reduced, or relocated rents, and increased competition in financial services. The author examines available data on money market, and bank interest rates for evidence of whether these things happened. He shows that as more and more countries liberalized, the level and dynamic behavior of developing-country interest rates converged to industrial-country norms. In the short term, volatility increased in both real, and nominal money market interest rates. Treasury bill rates, and bank spreads, evidently the most repressed, showed the greatest increase as liberalization progressed - shifting substantial rents from the public sector, and from favored borrowers. Whereas quoted bank spreads in industrial countries contracted somewhat in the late 1990s, spreads in developing countries remained much higher, presumably reflecting both market power, and the higher risks of lending in the developing world. There was no clear-cut change in mean rates of inflation, monetary depth, or GDP growth. If anything, there was a small average improvement in inflation, but a decline in monetary depth, and economic growth, relative to trends in industrial countries.